How consumers "see" a visually warm store: Differences between affective and cognitive processors. Issue 2 (4th December 2017) - Baek, Eunsoo; Choo, Ho Jung; Oh, Hyunjoo; Yoon, So‐Yeon
Abstract: Store atmosphere can influence shoppers' perceptions and behaviors. This research contributes to the literature by showing that a visually warm store atmosphere can induce psychological warmth perception among in‐store consumers. An empirical study was conducted to investigate the effect of warmth through a visually warm or cold store atmosphere on consumers' perceptions/behaviors and the moderating role of consumers' processing styles. Results ( N  = 181) showed that a visually warm (vs. cold) atmosphere induces the perception of intimacy toward the store among affective processors and the perception of assortment similarity among cognitive processors. Such perceptions were found to mediate the effect of the visually warm atmosphere on consumers' approach behaviors toward the store. Based on the grounded cognition theory, this study extends the current knowledge of the warmth experience on psychological perceptions to a retail context. Findings not only contribute to the extant literature of store atmospherics and retailing but they also offer practical guidelines for retailers and designers of store environments.